Effects of sustained Russian wheat aphid (Diuraphis noxia Mordvilko) feeding on leaf blades of wheat (Triticum aestivum L. cv Adamtas) - Matsiliza, Babalwa (Rhodes University, Faculty of Science, Botany Department, 2003)
Penetration of sink as well as source leaves of wheat plants by the Russian wheat aphid, Diuraphis noxia (Mordvilko) was investigated using light, fluorescence and transmission electron techniques, to determine the feeding strategies adopted by the aphid in penetrating and successfully feeding from the phloem, and to assess the structural effects of the probing and feeding behaviour of D. noxia on the feeding sites. Examination of aphid-infested sink, as well as source leaf tissue, showed that D.noxia probed in cells of the vascular bundle more frequently than mesophyll cells. Within the vascular bundle, thin-walled sieve tubes were visited (probed) more than the other cells. In sink leaf material, 68 of 82 (83%) stylets and stylet tracks encountered during the examination of 1000 serial sections (from 5 different plants) terminated in thin-walled sieve tubes and only 14 (17%) in thick-walled sieve tubes. Thin-walled sieve tubes were visited more significantly than thick-walled sieve tubes. However, examination of the aphid.,.infested sink leaf on a per centimetre basis, from the tip of the leaf, revealed that thick-walled sieve tubes in the area closest to the tip (0-2cm from the tip) were as attractive to the aphid as were thin-walled sieve tubes, with no significant difference in the number of times thick- and thin-walled sieve tubes were probed in this area. Some 2-4cm from the tip however, thinwalled sieve tubes were significantly more probed and therefore more attractive than thick-walled sieve tubes. Examination of 2000 serial sections using aphid-infested source leaf tissue, showed that the thin-walled sieve tubes were significantly more probed than thickwalled sieve tubes, along the whole leaf, expressed as a total of all leaves, as well as on a per centimetre basis along the length of the leaf, with 212 (95%) of 222 terminations within the thin-walled sieve tubes and only 10 (5%) in thick-walledsieve tubes. The aphid probed the small vascular bundles (loading bundles) many more times than intermediate or large transport vascular bundles, in sink as well as source leaf. Of a total of 82 stylets and stylet tracks encountered in sink leaf tissue, 31 terminated in small vascular bundles ang the remaining 28 and 16 were located within large and intermediate vascular bundles respectively. In source leaf tissue 121 of 222 stylets and stylet tracks encountered were associated with small vascular bundles and only 58 tracks and 43 tracks with intermediate and large vascular bundles, respectively. The effect of sustained RWA feeding on the transport capacity was examined after the application of 5,6 carboxyfluoresceine diacetate (5,6-CFDA) in control (sink and source leaf tissue) and aphid-infested (source) wheat leaves, using fluorescence microscopy. After 3h acropetal longitudinal transport of 5,6-CF had occurred in sink leaves in longitudinal veins, as well as a lateral transfer via cross veins and subsequent unloading into mesophyll cells close to the tip of the leaf was observed. In control leaf tissue, the fluorescence front was detected up to about 5cm from the point of application and was only associated with the phloem and not unloaded. In contrast, aphid-infested leaf tissue showed very little 5,6-CF transport, being limited to 2cm or less from the point of application. Structural damage to the phloem in general and to the sieve tubes in particular within of control and infested wheat leaves was investigated using transmission electron microscopy (TEM). In addition, leaf strips were mounted in aniline blue to visualise callose deposition using the fluorescence microscopy. At the TEM level. infested leaf tissue showed various abnormalities, which included destruction of cell contents, membrane damage and subsequent loss of cell contents. TEM studies suggest severe osmotic shock resulted from the aphid's probing. Examination of leaf tissue using fluorescence microscopy showed that there was very little characteristic aniline blue-stained callose visible in control leaf tissue, other than the thin diffuse patches along the sieve plates and punctate spots associated with pore plasmodesmatal areas and plasmodesmatal aggregates. In contrast, the aphid-infested leaf tissue was heavily callosed, with callose deposited not only within the phloem tissue but also in neighbouring vascular parE:}nchyma cells as well. The data collectively suggest that D. noxia feeds preferentially within thin-walled sieve tubes, within the small longitudinal vascular bundles in sink , as well source leaf tissue. Based upon the data presented here the thin-walled sieve tubes in the wheat leaf appear to be more attractive to the aphid and that they are probably more functional in terms of transport system and unlo?lding in sink leaves. Aniline blue stained leaf material that had previously hosted large aphid colonies showed evidence of extensive callose deposits 24 to 36h after the aphids were removed, suggesting that the aphids caused severe mechanical damage to the vascular tissue and mesohyll cells as well. Damage (transient or more permanent) and the subsequent deposition of wound callose, disrupted phloem transport and hence the export of photoassimilate from the leaves.
Keywords: Russian wheat aphid; Wheat -- Diseases and pests